Laboratory Liquefaction Test of Sand Based on Grain Size and Relative Density - Hakam, Abdul (Journal of Engineering and Technological Sciences, 2016)
Liquefaction due to strong earthquakes often occurs in sandy soil under low water table conditions with certain physical properties. The physical properties of sandy soil that give effect to liquefaction resistance include grain size and relative density. This paper presents the physical properties of sand soils related to their resistance to vibration. Vibration tests were conducted by using a shaking table. The acceleration and settlement of the samples were recorded during shaking. The tests were conducted with variation of soil density and mean grain size. The test results showed that average grain size and relative density of sand have a unique effect on liquefaction resistance. It can be concluded that there is a density limit with respect to the mean grain size of the sand particles associated with the liquefaction resistance for a certain acceleration.